Uji Kekerasan Resin Komposit Olahan Sendiri dengan Filler Hidroksiapatit dari Tulang Ikan Air Tawar - Nina Djustiana; Elin Karlina; Arief Cahyanto; Zulia Hasratiningsih; Rosidah Nurhayati (Jurnal Material Kedokteran Gigi, 2018)
Resin composite is one of the restoration materials used in dentistry. The study toward resin composite was being done to improve mechanical properties and the biocompatibilities, one of the ways by using hydroxyapatite filler. State of the aim of this study was to evaluate the hardness number of resin composite with hydroxyapatite filler from fresh water fish bones. The study was true experimental using five samples of resin composites processed with hydroxyapatite filler from fresh water fish bones and five samples of fabricated resin composites (GC Solare P) as a control. Hardness was evaluated using the Vickers microhardness testing machine (Leco). The average hardness number of resin composite processed was 18.384 VHN and resin composite made by factory was 27.952 VHN. The results were analyzed statistically by t independent (α=0.05) and showed significantly difference between resin composite processed with hydroxyapatite filler from fresh water fish bones compared to fabricated resin composite. The conclusion from this study showed that the hardness number of resin composite processed with hydroxyapatite filler from fresh water fish bone is lower than fabricated resin composite.